Activatable molecular probes for fluorescence-guided surgery, endoscopy and tissue biopsy. (20th December 2021) - Zhang, Yan; Zhang, Guopeng; Zeng, Ziling; Pu, Kanyi
Abstract : We highlight the development of activatable molecular probes that trigger the optical signals toward biomarkers, allowing real-time, dynamic visualization of lesions and margins for guided-surgery, endoscopy and tissue biopsy with molecular precision. Abstract : The real-time, dynamic optical visualization of lesions and margins ensures not only complete resection of the malignant tissues but also better preservation of the vital organs/tissues during surgical procedures. Most imaging probes with an "always-on" signal encounter high background noise due to their non-specific accumulation in normal tissues. By contrast, activatable molecular probes only "turn on" their signals upon reaction with the targeted biomolecules that are overexpressed in malignant cells, offering high target-to-background ratios with high specificity and sensitivity. This review summarizes the recent progress of activatable molecular probes in surgical imaging and diagnosis. The design principle and mechanism of activatable molecular probes are discussed, followed by specific emphasis on applications ranging from fluorescence-guided surgery to endoscopy and tissue biopsy. Finally, potential challenges and perspectives in the field of activatable molecular probe-enabled surgical imaging are discussed.